Compatibility of fungicides with Trichoderma asperelloides and Azospirillum brasilense - Joseph, Louis Antoniel; Sousa, Kellem Ângela Oliveira de; Chagas Júnior, Aloísio Freitas; Luc, Frantzdy (Scientia Agraria Paranaensis, 2022)
The use of fungicides to control agricultural diseases has been increasing in agriculture. Thus, the biological control using fungus is an effective tool in the integrated diseases management. This study aimed to evaluate the compatibility of fungicides Certeza, Apron and Vitavax on the microorganisms Trichoderma asperelloides and Azospirillum brasilense. The experiments were conducted in vitro in a completely randomized design with a factorial arrangement 2 x 3 with three replications. The first factor composed of two doses and the second referred to the fungicides. The microorganisms were developed in PDA medium. After the medium has solidified, in a flow layer 10 µL of the fungal solution was added to each plate with the aid of an automatic pipette (D1, recommended dose; D2, double of recommended dose). Then, each Petri plate was centrally inoculated with a disc of Trichoderma asperelloides, in addition to the uninoculated control. For Azospirillum brasilense, the colony surface was scraped with the aid of a sterilized Drigalsky loop. Then, the filter of discs paper was dipped in the fungicides solution and placed on the medium surface. After this process, the plates were incubated in a BOD (Biochemical Oxygen Demand) at 26±2ºC and photoperiod 12 h. The parameters evaluated were a mycelial growth and sporulation. The results showed that there was no significant interaction between the factors. The fungicides Certeza (Tiofanato metílico + Fluazinam), Apron (Fludioxonil + Metalaxil-M) and Vitavax (Carboxina + Tiram) are considered compatible with Trichoderma asperelloides and Azospirillum brasilense. The fungicides can be used in an integrated disease management practices, priority must be given to use the products that have been shown to be less harmful.